1987
DOI: 10.1111/j.1469-8749.1987.tb02508.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density in Myelomeningocele: The Effects of Ambulatory Status and Other Factors

Abstract: SUMMARY Measurements were made of distal radius, mid‐radius, tibia and metatarsal bone‐density of 80 patients with myelomeningocele (17 thoracic, six L1/L2, 13 L3, 30 L4, 14 L5/sacral). For the upper extremity the bone density primarily was low in the thoracic patients, but in the tibia and metatarsal it showed a more linear correlation with neurological levels. The effect of age was highly significant at all sites; after controlling for this, the neurological level was a significant determinant of bone densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 23 publications
3
39
1
Order By: Relevance
“…Twenty-four of 37 children (64.8%) in the present study had at least one LDF Z-score less than 2 standard deviations below the age-and-sexmatched mean. Our observations confirm those of both Rosenstein et al [11] and Quan et al [10] looking at single photon absorptiometry. Apkon et al [1], using DXA as we did, classified patients not according to ISCD recommendations for children (B À2 SD is ''low bone density for age), but rather used the World Health Organization classification for postmenopausal females [2] (B À2.5 SD is ''osteoporosis'' and B À1 SD is ''osteopenia'') [7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Twenty-four of 37 children (64.8%) in the present study had at least one LDF Z-score less than 2 standard deviations below the age-and-sexmatched mean. Our observations confirm those of both Rosenstein et al [11] and Quan et al [10] looking at single photon absorptiometry. Apkon et al [1], using DXA as we did, classified patients not according to ISCD recommendations for children (B À2 SD is ''low bone density for age), but rather used the World Health Organization classification for postmenopausal females [2] (B À2.5 SD is ''osteoporosis'' and B À1 SD is ''osteopenia'') [7].…”
Section: Discussionsupporting
confidence: 92%
“…Rosenstein et al [11] and Quan et al [10] examined bone density in children with myelomeningocele using 125 I single photon absorptiometry. Rosenstein et al found bone density of both upper and lower extremities in patients with spina bifida related to neurologic level and ambulatory status [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…postoperatively). 1,[4][5][6] Our primary aim in this study was to examine the frequency and characteristics of fractures in paediatric patients with spina bifida. A secondary aim was to identify other variables that may contribute to the presence of fractures, such as neurological level, shunted hydrocephalus, syringomyelia, type of ambulation, mechanism of injury, and prolonged immobilization.…”
mentioning
confidence: 99%
“…In patients who are already disabled and subject to frequent surgical interventions, osteoporosis-related fractures result in a vicious cycle in which further immobilization heightens the risk of multiple fractures. [2][3][4][5][6][7] In childhood and adolescence, the formation of bone prevails; 8 consequently, childhood and adolescence constitute critical periods for the foundation of a lifetime of bone health. Failure to achieve peak bone mass has been linked to an increased risk of osteoporosis and fracture in adulthood.…”
Section: Introductionmentioning
confidence: 99%